Assessing a Metacognitive Account of Associative Memory Impairments in Temporal Lobe Epilepsy. (19th September 2016) - Illman, Nathan A.; Kemp, Steven; Souchay, Céline; Morris, Robin G.; Moulin, Chris J. A.
Abstract : Previous research has pointed to a deficit in associative recognition in temporal lobe epilepsy (TLE). Associative recognition tasks require discrimination between various combinations of words which have and have not been seen previously (such as old-old or old-new pairs). People with TLE tend to respond to rearranged old-old pairs as if they are "intact" old-old pairs, which has been interpreted as a failure to use a recollection strategy to overcome the familiarity of two recombined words into a new pairing. We examined this specific deficit in the context of metacognition, using postdecision confidence judgements at test. We expected that TLE patients would show inappropriate levels of confidence for associative recognition. Although TLE patients reported lower confidence levels in their responses overall, they were sensitive to the difficulty of varying pair types in their judgements and gave significantly higher confidence ratings for their correct answers. We conclude that a strategic deficit is not at play in the associative recognition of people with TLE, insofar as they are able to monitor the status of their memory system. This adds to a growing body of research suggesting that recollection is impaired in TLE, but not metacognition.